A Response to Punti and Dingel's Critique of the Validity of the Intercultural Development Inventory for BIPOC Students. Comment on Punti, G.; Dingel, M. Rethinking Race, Ethnicity, and the Assessment of Intercultural Competence in Higher Education. Educ. Sci. 2021, 11, 110 - Mitchell R. Hammer (MDPI AG, 2022)
Addressing social inequity and increasing intercultural competence is a critical challenge in the 21st century. This work should be informed by rigorous, scientifically grounded research, accurate interpretations of that research, and the implementation of policies and training that are based upon the integrity of such research efforts. The Intercultural Development Inventory (IDI), because of its psychometric integrity, is one such assessment tool that is used to pursue these challenges in higher education. The psychometric integrity of the IDI is unequivocally situated within the Standards for Educational and Psychological Testing (Standards for Educational and Psychological Testing 2014. American Educational Research Association [AERA], American Psychological Association [APA], and the National Council on Measurement in Education [NCME]). Punti and Dingel assert that the IDI is not valid specifically for Black, Indigenous, and People of Color (BIPOC) university students because it does not take into account the experience of being a minority/ethnic group member vis-à-vis racism and inequality. It is troubling that Punti and Dingel's critique (1) is based on their use of an interview methodology that does not comport with the Standards for Educational and Psychological Testing and (2) ignores the scientific evidence supporting the cross-cultural validity of the IDI with BIPOC.